Phylogenetic aspects in the higher classification of the subfamily Catocalinae (Lepidoptera, Noctuidae). - Speidel, Wolfgang; Naumann, Clas Michael (Contributions to Entomology = Beiträge zur Entomologie, 1995)
The subfamily Catocalinae is shown to be based on a typological concept. A re-evaluation of the subfamily as a whole is not yet possible. Thus, it appears appropriate to define smaller monophyletic units within the subfamily. Based on the shape of the internal female genitalia (ductus receptaculi), it is shown that the Euclidiini form a monophylum. We do not think that it is advisable to incorporate the Melipotini and Eulepidotini in that monophylum, as we could not find any synapomorphies for these tribes, which proved to be rather different structurally.